The decimation of livestock :|the Ottoman East in the Great War - Kahvecioğlu, Batuhan. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2021., 2021)
This thesis investigates the reasons and effects of the small-cattle and draft animals' deaths during the Great War from an environmental history perspective. Focusing on the Eastern Ottoman region, it shows that the state's taxation policies, region's geography, climate, limited veterinary services, and contagious animal diseases were the main reasons behind the decimation of animals. These animal deaths affected the Ottoman government's policies toward animals and created local noncompliance with the government's decrees, showing the bilateral relationship between the environment and population.
Keywords: Animals -- Ottoman Empire, 1288-1918.; Livestock -- Turkey.